Advances in design and manufacture of stretchable electronics. (1st June 2022) - Gillan, Liam; Hiltunen, Jussi; Behfar, Mohammad H.; Rönkä, Kari
Abstract: Flexible and stretchable electronics present opportunities for transition from rigid bulky devices to soft and conformal systems. However, such technology requires mechanical design and integration strategies to enhance robustness and form factor. In addition, scalable and reliable fabrication pathways are needed to facilitate the high volume manufacturing required to satisfy a growing market demand. This report describes recent advances in design, manufacture, and reliability of flexible and stretchable electronics technology. Flexible concept devices for physiological monitoring are introduced, before discussion of high throughput fabrication of stretchable electronics, then hybrid integration of conventional rigid components on stretchable carrier substrates with an emphasis on a need for further developments in device reliability testing procedures. Finally, consideration is given to transition options for more eco-conscious device constituents. These cases progress flexible and stretchable electronics towards robust, fully integrated, unobtrusive devices incorporating sustainable components.